2021
DOI: 10.2147/rmhp.s311334
|View full text |Cite
|
Sign up to set email alerts
|

Who are the “Real” Experts? The Debate Surrounding COVID-19 Health Risk Management: An Israeli Case Study

Abstract: Background The uncertainty surrounding the COVID-19 crisis and the different approaches taken to manage it have triggered scientific controversies among experts. This study seeks to examine how the fragile nature of Israeli democracy accommodated differences of opinion between experts during the COVID-19 crisis. Objective To map and analyze the discourse between experts surrounding issues that were the topic of scientific controversy. To examine the viewpoints of the pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…Furthermore, epidemiological crises are often marked by ego conflicts between experts from the various fields. See, for example, the disagreements among the various experts during the COVID-19 crisis, as exemplified in our research, 150 such that each expert thinks he or she represents “pure science”, which is of course erroneous. Indeed, when science is associated with lifestyle, politics and values assume a central role.…”
Section: Discussionmentioning
confidence: 86%
“…Furthermore, epidemiological crises are often marked by ego conflicts between experts from the various fields. See, for example, the disagreements among the various experts during the COVID-19 crisis, as exemplified in our research, 150 such that each expert thinks he or she represents “pure science”, which is of course erroneous. Indeed, when science is associated with lifestyle, politics and values assume a central role.…”
Section: Discussionmentioning
confidence: 86%
“…In a study that examined the scientific discourse in Israel at the beginning of the COVID-19 pandemic, we found that there was no dialogue between opposition and coalition experts. Moreover, the coalition experts labeled the experts who criticized them as “coronavirus deniers” and “anti-vaxxers” ( 62 ). During the vaccination campaign in Israel, the health system rejected criticism from opposition experts in several ways: It refused to engage in discourse with opposition experts ( 90 ).…”
Section: Discussionmentioning
confidence: 99%
“…Each of these groups has an additional explanatory variable. Among those who are conservative, the additional explanatory variable is age, such that those age 45 and above show more support for the government, while those age 44 and younger give more support to the opposition's positions ( 62 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The elderly were instructed not to come into work but to work remotely as much as possible, to use delivery services or family members for food and medication purchases and to avoid any unnecessary meetings. It was shown that this age group strictly adhered to the guidelines compared to the general population [1], [4], [5].…”
Section: Introductionmentioning
confidence: 99%